Analisis Faktor Psikologis Dan Kesehatan Mental Wisatawan: Studi Kasus Pada Aktivitas Healing di Wana Wisata Ranca Upas - Indrianty, Septy; Wineske Putri, Bianca Keyko (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
This study aims to explore the psychological factors and mental health conditions of tourists visiting Wana Wisata Ranca Upas, as well as to understand the efforts made by the management to facilitate tourists in engaging in mental health recovery activities (healing). The research uses a qualitative approach with a case study analysis. The variables used are psychological factors and mental health. Data collection was carried out through observation, interviews, and documentation. The results of this study show that there are various psychological factors underlying tourists' motivations to visit Wana Wisata Ranca Upas, including the desire to engage in healing activities, FOMO (fear of missing out), and quality time with a partner. Furthermore, regarding mental health, tourists reported experiencing changes in their mental health condition. Before visiting Wana Wisata Ranca Upas, their mental condition was considered poor, but after visiting, their mental health significantly improved. Additionally, efforts made by the management to facilitate tourists' healing activities have been quite good, but there are shortcomings in its implementation, namely the lack of effective promotion of the healing forest program. Therefore, the management needs to intensify promotion, maintain consistency in destination management, continue to innovate by creating new programs in line with trends, create innovative healing activity packages, and collaborate with more travel agents.